Query Based Text Summarization - Mangalampagti, Sindhura; Ponnuru, Raveendra Babu (International journal of recent technology and engineering, 2019)
Now a day’s, The advancement of technology implies the large amount of online textual Information, this leads to a need for Text Summarizers which can provide important textual data from large data source like www, into a well-structured document formats. It becomes an alive analysis activity to specify the related data that is retrieved from huge set of documents which are established from various sectors like social media. Text summary is the action of precise the documents by protecting the key concepts of the text. This process can be accomplished via extractive summary and abstractive summary. In this paper, we suggested summarization technique that is to be applied on online information depending upon the User required Document.